Use of aortic flow indexes derived from transthoracic echocardiography to evaluate response to a fluid challenge in anesthetized dogs - de Oliveira, Guillermo C.V. [UNESP]; Teixeira-Neto, Francisco J. [UNESP]; Dalmagro, Tábata L. [UNESP]; Alfonso, Angélica [UNESP]; Celeita-Rodríguez, Nathalia [UNESP]; Lobo, César P.C. [UNESP]; Lourenço, Maria L.G. [UNESP] (Elsevier, 2021)
Objective: To evaluate the ability of transthoracic echocardiographic aortic flow measurements to discriminate response to a fluid challenge (FC) in healthy anesthetized dogs. Study design: Prospective experimental study. Animals: A total of 48 isoflurane-anesthetized dogs (14.2–35.0 kg) undergoing elective surgery. Methods: Fluid responsiveness was evaluated before surgery by FC (lactated Ringer's 10 mL kg–1 intravenously over 5 minutes). Percentage increases in transpulmonary thermodilution stroke volume (ΔSVTPTD) >15% from values recorded before FC defined responders to volume expansion. A group of 24 animals were assigned as nonresponders (ΔSVTPTD ≤15%). When ΔSVTPTD was >15% after the first FC, additional FC were administered until ΔSVTPTD was ≤15%. Final fluid responsiveness status was based on the response to the last FC. Percentage increases after FC in aortic flow indexes [velocity time integral (ΔVTIFC) and maximum acceleration (ΔVmaxFC)] and in mean arterial pressure (ΔMAPFC) were compared with ΔSVTPTD. Results: After one FC, 24 animals were responders. For nonresponders, ΔSVTPTD was ≤15% after one, two and three FCs in eight/24, 15/24 and one/24 animals, respectively. The FC that defined responsiveness increased ΔSVTPTD by 29 (18–53)% in responders and by 8 (–3 to 15)% in nonresponders [mean (range)]. The area under the receiver operating characteristics curve (AUROC) of ΔVTIFC (0.901) was larger than the AUROCs of ΔVmaxFC (0.774, p = 0.041) and ΔMAPFC (0.519, p < 0.0001). ΔMAPFC did not predict responsiveness (p = 0.826). Best cut-off thresholds for discriminating responders, with respective zones of diagnostic uncertainty (gray zones) were >14.7 (10.8–17.6)% for ΔVTIFC and >8.6 (–0.3 to 14.7)% for ΔVmaxFC. Animals within the gray zone were 17% (ΔVTIFC) and 50% (ΔVmaxFC). Conclusions and clinical relevance: Changes in VTI induced by FC can determine responsiveness with reasonable accuracy in dogs and could play an important role in goal-directed fluid therapy.
Keywords: fluid responsiveness; goal-directed fluid therapy; velocity time integral